Synthesis of Heat-Integrated Water Networks: Case Study with Sensitivity Analysis - Nidret Ibric (AIDIC Servizi S.r.l., 2021)
This work addresses the synthesis of heat-integrated water networks (HIWNs) by using a superstructure optimisation approach. A recently developed mixed-integer nonlinear programming (MINLP) model and an iterative solution strategy are applied in this work to a case study of HIWN. The objective function of the MINLP model is to minimise the network total annualised cost (TAC) comprising operating and investment costs. As there are trade-offs between operating and investment costs, good solutions can be obtained if the TAC is minimised by simultaneously exploring all water and heat integration opportunities within the network. A case study with sensitivity analysis is solved by analysing the impact of freshwater and utility costs on the network design and key performance indicators. The results indicate that in cases of low freshwater cost increased freshwater usage is forced and thus lowering wastewater regeneration/recycling and wastewater treatment cost. Increased freshwater flowrate is related to an increase of HEN investment. The high cost of freshwater could produce solutions with lower freshwater consumption compared to base case depending on utility cost and wastewater treatment cost. However, a decrease in freshwater consumption increases wastewater regeneration costs.